High-energy doping method for surface of high polymer material

By performing high-energy doping treatment on the surface of polymer materials and using segmented ion implantation technology to form a gradient doping layer, the problem of poor bonding force between the polymer material substrate and the metal layer is solved, and the mechanical properties and service life of the metal layer are significantly improved.

CN119697904APending Publication Date: 2025-03-25SOUTHWESTERN INST OF PHYSICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411880369.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The molecular interaction between the polymer material substrate and the metal layer is weak, resulting in the interface being prone to failure when it is subjected to external forces or heat loads, affecting the mechanical properties and service life of the metal layer.

Method used

Using a high-energy doping method of polymer materials on the surface, after cleaning, baking and vacuum heating, segmented ion implantation is carried out, and inorganic material elements, such as metal ions and gas ions are introduced to form a gradient doping layer.

Benefits of technology

The molecular interaction between the substrate and the metal layer is improved, the bearing capacity and mechanical properties of the interface are enhanced, the service life of the metal layer is extended, and the film-based binding performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119697904A_ABST
    Figure CN119697904A_ABST
Patent Text Reader

Abstract

The invention discloses a high-energy doping method for the surface of a high polymer material, and relates to the technical field of flexible circuit boards. A high-energy doping method for the surface of a high polymer material comprises the following steps: S1, cleaning and baking a base material, and then carrying out vacuum heating treatment; and S2, carrying out segmented ion implantation on the surface of the base material through inorganic material elements to obtain the high-energy-doped high polymer material of which the relative content is gradually changed and which is high-energy-doped with the inorganic material elements. The problems that the binding force between the substrate and the metal layer is poor, the mechanical property of the metal layer is poor, and the service life of the metal layer is short are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flexible circuit boards, and in particular to a method for high-energy doping on the surface of a polymer material. Background Art

[0002] In the preparation process of flexible circuit boards, the bonding of polymer films and metals is a very critical step. The traditional preparation methods are gluing and hot pressing. The gluing method is to position the copper foil and the adhesive material (epoxy resin) by CCD recognition and punching, and then combine, bake and cure to obtain a connected and formed substrate; the hot pressing method is to attach the hot pressing adhesive to the flexible circuit board, hot press it, and then punch it into the required shape and then hot press it onto the metal sheet to obtain the entire substrate. Both methods have the problems of high preparation temperature, high cost, and limited thickness (not thin, mostly millimeter level), and the use of adhesives cannot be avoided, which seriously limits the overall thermal conductivity and the temperature range of the product, making it difficult to meet the current demand for ultra-thin and high-precision circuit boards.

[0003] Based on this, an adhesive-free circuit board preparation technology has been developed. It mainly grows a layer of metal film directly on a polymer substrate by electroplating, chemical plating or vacuum coating, thereby completing the transformation from a polymer substrate / adhesive / copper foil three-layer flexible circuit board (3L-FPC) to a polymer substrate / copper foil two-layer flexible circuit board (2L-FPC). The two-layer flexible circuit board eliminates the thermal resistance influence of adhesives and halogen flame retardants, and can have excellent heat resistance under the premise of lead-free / high temperature process, maintain a small deformation rate at a temperature of up to 300°C, and has strong dimensional stability and more sophisticated circuit design feasibility.

[0004] However, due to the strong chemical inertness of the substrate (mostly high molecular polymers such as polyimide or polyester) and the large difference in physical and chemical properties between the substrate and the metal layer (mostly copper), the molecular interaction between the two is weak, and the interface is prone to failure when subjected to external force or heat load; in addition, the surface of high molecular polymer materials is often too smooth, making it difficult for metal droplets to infiltrate them, which ultimately affects the uniform distribution and transfer of external loads from the substrate to the bearing metal layer, limiting the mechanical properties and service life of the metal layer. Therefore, the peel strength between the film and the substrate has become the main factor restricting the performance and life of the flexible circuit board. Although it has been improved through measures such as coating structure design and coating process optimization, the problem of weak adhesion at the interface is still a key obstacle to the development of ultra-thin, high-precision two-layer flexible circuit boards.

[0005] Although the existing plasma technology can improve the problem of drastic changes in the properties of heterogeneous materials at the interface to a certain extent, it still has shortcomings. The membrane-substrate bonding strength is still a difficult problem that needs to be solved in the field of surface engineering. Based on this, it is urgent to propose and develop technologies that are more adaptable and have better improvement effects. Summary of the invention

[0006] The technical problem to be solved by the present invention is that the molecular interaction between the substrate and the metal layer of the existing polymer material is weak, and the interface is prone to failure when subjected to external force or heat load; the surface of the polymer material is often too smooth, making it difficult for the metal droplets to infiltrate it, which ultimately affects the uniform distribution and transmission of the external load from the substrate to the bearing metal layer, limiting the mechanical properties and service life of the metal layer. The purpose is to provide a method for high-energy doping on the surface of a polymer material, which solves the problems of poor bonding between the substrate and the metal layer, poor mechanical properties of the metal layer, and short service life of the metal layer.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0009] S1, cleaning and baking the substrate, and then performing vacuum heating treatment;

[0010] S2. Performing segmented ion implantation of inorganic material elements on the surface of the substrate to obtain a polymer material doped with inorganic material elements having a gradually varying relative content.

[0011] As a possible design, the cleaning in the above step S1 specifically involves cleaning the substrate with an organic cleaning solvent, and the baking specifically involves baking the cleaned substrate at 80 to 120° C. for 12 to 24 hours.

[0012] As a possible design, the vacuum heating treatment in step S1 is to heat the baked substrate at 2×10 -3 ~4×10 -3 Pa vacuum, heat to 100-120°C and keep warm for 1-4h.

[0013] Vacuum heating treatment can ensure that the gas in the substrate escapes, avoiding the impact on subsequent ion implantation; vacuum conditions reduce the introduction of external impurities, ensuring the cleanliness of the material surface during the implantation process, thereby improving the purity and controllability of doping; heating can also help to make the overall temperature of the material uniform, which is crucial for the uniformity of subsequent ion implantation, avoiding differences in implantation depth or concentration caused by uneven temperature.

[0014] As a possible design, the segmented ion implantation in step S2 is performed at a vacuum degree of 5×10 -3 Pa is carried out below.

[0015] As a possible design, the inorganic material elements in the above step S2 include metal ions and gas ions.

[0016] As a possible design, when the inorganic material element is a metal ion, the cathode metal for injection includes a metal element and an alloy;

[0017] The metal element includes copper, aluminum, titanium, chromium, nickel or silver;

[0018] The alloy package is an alloy containing copper, aluminum, titanium, chromium, nickel or silver, and the alloy also includes rare earth elements, rare earth element alloys and rare earth element oxides, and the rare earth element is one or more of scandium, yttrium, praseodymium, lanthanum and cerium.

[0019] As a possible design, when the inorganic material elements are gas ions, the injected gas includes one or more of argon, oxygen, nitrogen and hydrogen.

[0020] As a possible design, the above-mentioned segmented ion implantation is specifically segmented gradual ion implantation, and the segmented gradual ion implantation includes a low-content doping stage, a medium-content doping stage and a high-content doping stage.

[0021] As a possible design, the voltage of the low-content doping stage is 10-30KV, the injection time is 5-60min, and the injection layer thickness is 20-80nm; the voltage of the medium-content doping stage is 10-20KV, the injection time is 5-40min, and the injection layer thickness is 15-70nm; the voltage of the high-content doping stage is 0-10KV, the injection time is 5-40min, and the injection layer thickness is 15-70nm.

[0022] As a possible design, the total thickness of the low-content doping stage, the medium-content doping stage and the high-content doping stage is 50 to 220 nm, the total injection time is 15 to 140 min, and the total injection dose is 1×10 15 ~1×10 17 Pieces / cm 2 .

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] The present invention adopts ion implantation technology to dope the polymer substrate with inorganic material elements with gradually varying contents. The doped medium ions are accelerated and carry high energy to elastically or inelasticly collide with the surface atoms of the substrate, resulting in long chain cleavage, short chain flipping and translation, and reconstruction, and finally the structural distribution and surface properties of the surface of the material change. Through ion implantation, the doped ions are driven to be deeply implanted in the substrate to form a "pinning" strengthening effect. Compared with other surface modification technologies, the modified layer produced by this technology is rooted in the substrate, and there is no hidden danger of film falling off. The interface layer is further widened on the basis of producing a "pseudo-diffusion layer", weakening the difference gradient of the physicochemical properties of the interface layer, thereby improving the molecular interaction between the substrate and the metal layer, avoiding interface failure, and improving the uniform distribution and transmission of the applied load from the substrate to the bearing metal layer.

[0025] In addition, the present invention adopts segmented ion implantation during ion implantation, so as to perform graded regulation on the energy of the doped ions, thereby adjusting the relative content of inorganic elements in the doped injection layer, so that the content of inorganic elements injected into the modified layer gradually increases from the inner layer to the outer layer, thereby reducing the physical and chemical differences and avoiding the adverse effects caused by drastic changes in characteristics.

[0026] The doped modified layer obtained by segmented ion implantation in the present invention has properties such as gradual hardness, strength, thermal expansion coefficient, etc., and can be tightly combined with the substrate and the surface functional film through mechanical biting, which can enhance the adhesion between the polymer substrate and the surface coating, improve the problem of weak bonding at the interface, and provide a new solution for the development of ultra-thin and high-precision two-layer flexible circuit boards.

[0027] The method of the invention has simple operation process and direct and effective composition regulation, is applicable to the surface modification of all flexible and non-flexible polymer materials, and has huge economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0029] Figure 1 The cross-sectional structure diagram of the high molecular weight material doped with inorganic material elements according to Example 2 of the present invention;

[0030] Figure 2 This is a comparison diagram of the copper film fracture morphology and composition of the high-energy doped polymer material (b) and the undoped polymer material (a) of Example 2 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0032] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0033] S1, cleaning and baking the substrate, and then performing vacuum heating treatment;

[0034] S2. Performing segmented ion implantation of inorganic material elements on the surface of the substrate to obtain a polymer material doped with inorganic material elements in high energy.

[0035] In some embodiments of the present invention, the cleaning in step S1 is specifically to clean the substrate with an organic cleaning solvent, and the baking is specifically to bake the cleaned substrate at 80-120° C. for 12-24 hours.

[0036] Preferably, the organic cleaning solvents include, but are not limited to, alcohols, ketones, alkanes, benzenes and ethers. Specifically, alcohols include methanol, acetone, isopropanol and anhydrous ethanol, ketones include methyl ethyl ketone, methyl butyl ketone, benzenes include n-hexane, dichloromethane, chlorofluorocarbons, etc., and ethers include petroleum ether, etc.

[0037] Preferably, the baking temperature can be any value within the range of 80 to 120° C., including but not limited to 85° C., 88° C., 91° C., 93° C. and 118° C., preferably 100° C. The baking time can be any value within the range of 12 to 24 hours, including but not limited to 18 hours, 15 hours, 13 hours and 22 hours.

[0038] Cleaning can remove impurities such as grease, dust, and residual glue on the surface of the substrate, which may interfere with the precise injection of subsequent ions and cause uneven doping. Baking can thoroughly remove surface moisture and other volatile substances, ensure that the material surface is dry, and avoid moisture causing problems in a vacuum environment.

[0039] Preferably, after cleaning, the substrate is dried by compressed air to remove surface moisture.

[0040] In some embodiments of the present invention, the vacuum heating treatment in step S1 is to heat the baked substrate at 2×10 -3 ~4×10 -3 Pa vacuum, heat to 100-120°C and keep warm for 1-4 hours. The vacuum degree can be 2×10 -3~4×10 - 3 Any value within Pa, including but not limited to 2.5×10 -3 Pa, 2.8×10 -3 Pa, 3.1×10 -3 Pa and 3.5×10 -3 The heating temperature may be any value within the range of 80 to 120° C., including but not limited to 85° C., 88° C., 91° C., 93° C. and 118° C., preferably 100° C. The holding time may be 3 h, 2 h or 2.5 h.

[0041] Vacuum heating treatment can ensure that the gas in the substrate escapes, avoiding the impact on subsequent ion implantation; vacuum conditions reduce the introduction of external impurities, ensuring the cleanliness of the material surface during the implantation process, thereby improving the purity and controllability of doping; heating can also help to make the overall temperature of the material uniform, which is crucial for the uniformity of subsequent ion implantation, avoiding differences in implantation depth or concentration caused by uneven temperature.

[0042] In some embodiments of the present invention, the segmented ion implantation in step S2 is performed at a vacuum degree of 5×10 -3 Preferably, the vacuum degree can be 5×10 -4 Any value below Pa, including but not limited to 4×10 -3 Pa, 3×10 -3 Pa, 3×10 -3 Pa and 1×10 -3 Pa.

[0043] The inventors have found that the smaller the vacuum degree, the fewer impurity ions are in the chamber; if the vacuum degree is greater than this, the impurity ions will form an obstacle on the injection path of the metal ions, affecting the speed, angle and injection efficiency of the metal ions.

[0044] In some embodiments of the present invention, the inorganic material elements in step S2 include metal ions and gas ions.

[0045] The injection of metal ions can lay the foundation for subsequent processing steps, forming pinning reinforcement and buffer layers, thereby reducing the drastic changes in the physical and chemical properties between heterogeneous materials at the interface; the injection of gas ions can enhance the mechanical properties of the substrate, such as hardness, strength, and wear resistance.

[0046] In some embodiments of the present invention, when the inorganic material element is a metal ion, the cathode metal for injection includes a metal element and an alloy;

[0047] The metal element includes copper, aluminum, titanium, chromium, nickel or silver;

[0048] The alloy package is an alloy containing copper, aluminum, titanium, chromium, nickel or silver, and the alloy also includes rare earth elements, rare earth element alloys and rare earth element oxides, and the rare earth element is one or more of scandium, yttrium, praseodymium, lanthanum and cerium.

[0049] The injected rare earth elements are added as catalytic elements in trace amounts.

[0050] In some embodiments of the present invention, when the inorganic material elements are gas ions, the injected gas includes one or more of argon, oxygen, nitrogen and hydrogen.

[0051] In some embodiments of the present invention, the above-mentioned segmented ion implantation is specifically segmented gradual ion implantation, which includes a low-content doping stage, a medium-content doping stage and a high-content doping stage, and a doping injection layer is formed after doping in each stage.

[0052] By sequentially gradient doping with low, medium and high contents, doping injection layers with different doping amounts are formed, so that the doped elements are deeply embedded in the substrate. Such a smooth transition can reduce the physical and chemical differences, avoid the adverse effects caused by drastic changes in characteristics, strengthen the adhesion with the metal layer, and strengthen the combination of the substrate and the surface functional film through the mechanical bite between the doping injection ions and the internal structure of the substrate, further improving the adhesion strength between the polymer substrate and the surface coating.

[0053] In some embodiments of the present invention, the voltage of the low-content doping stage is 10-30KV, the injection time is 5-60min, and the injection layer thickness is 20-80nm; the voltage of the medium-content doping stage is 10-20KV, the injection time is 5-40min, and the injection layer thickness is 15-70nm; the voltage of the high-content doping stage is 0-10KV, the injection time is 5-40min, and the injection layer thickness is 15-70nm.

[0054] By adjusting the processing parameters of low-content doping, medium-content doping and high-content doping, a gradual concentration gradient can be formed. This is because the inventors found that if deposited directly, due to the difference in properties between the substrate and the coating, such as hardness difference and thermal expansion coefficient difference, the coating will fall off. By first injecting metal ions on the surface of the substrate, the surface hardness of the substrate is adjusted under the action of solid solution strengthening and pinning strengthening, and a concentration and hardness gradient layer can be prepared by controlling the conditions at each stage, so that the coating has a process of stress transfer and release when subjected to mechanical loads, and when subjected to thermal loads, thermal expansion also has a slow release space. And the inventors have found that the influence of the processing parameters at each stage on the coating performance is not a simple linear relationship, but needs to be obtained by comprehensive adjustment, and is related to the injection depth, concentration, voltage and time.

[0055] Preferably, the voltage of the low-content doping stage is 15-25KV, the injection time is 10-40min, and the injection layer thickness is 30-70nm; the voltage of the medium-content doping stage is 13-18KV, the injection time is 15-30min, and the injection layer thickness is 30-60nm; the voltage of the high-content doping stage is 3-8KV, the injection time is 10-30min, and the injection layer thickness is 20-60nm.

[0056] Preferably, the relative content (mass fraction) of inorganic elements in the low-content doping injection layer is 0-5%, the content of inorganic elements in the medium-content doping injection layer is 5-10%, and the relative content of inorganic elements in the high-content doping injection layer is greater than 10%.

[0057] More preferably, the relative content of inorganic elements in the low-content doping injection layer is 3%, the relative content of inorganic elements in the medium-content doping injection layer is 8%, and the relative content of inorganic elements in the high-content doping injection layer is 15%.

[0058] In some embodiments of the present invention, the total thickness of the low-content doping stage, the medium-content doping stage and the high-content doping stage is 50-220 nm, the total implantation time is 15-140 min, and the total implantation dose is 1×10 15 ~1×10 17 Pieces / cm 2 .

[0059] The total thickness can be any value within the range of 50 to 200 nm, including but not limited to 80 nm, 110 nm, 150 nm and 180 nm; the total injection time can be any value within the range of 15 to 140 min, including but not limited to 30 min, 80 min, 120 min and 130 min; the total injection dose can be 1×10 15 ~1×10 17 Pieces / cm 2 Any value within, including but not limited to 5×10 16 Pieces / cm 2 , 3×10 16 Pieces / cm 2 and 2×10 15 Pieces / cm 2 The total implantation dose is preferably 3×10 16 ~8×10 16 Pieces / cm 2 .

[0060] The substrate in the following embodiments is polyetheretherketone (PEEK), but the present invention can be applied to any polymer material, and the following embodiments are only examples.

[0061] Example 1

[0062] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0063] S1. The substrate was cleaned with 1003 organic solvent cleaning agent and anhydrous ethanol ultrasonic cleaning for 15 minutes each, dried with compressed air for 10 minutes, baked at 80°C for 12 hours, and then placed in a vacuum heating furnace and pre-evacuated to a vacuum chamber with a background vacuum of 2×10 -3 Pa, vacuum heating treatment heated to 100 ° C, keep warm for 1h;

[0064] S2, evacuate the surface of the substrate to a vacuum degree of 5×10 -4 After the temperature is below Pa, the copper cathode source switch is turned on, and inorganic material elements (copper ions) are injected in stages. After the injection is completed, the discharge is stopped, and the vacuum is maintained until the vacuum chamber temperature drops to room temperature. Then, the workpiece is taken out to obtain a polymer material with high energy doping of inorganic material elements.

[0065] The voltage of the low-content doping stage is 25KV, the injection time is 30min, and a low-content doping injection layer is obtained, and the injection layer thickness is 20 to 80nm;

[0066] The voltage of the medium-content doping stage is 15KV, the injection time is 30min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0067] The voltage of the high-content doping stage is 10KV, the injection time is 20min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0068] The total injection time was 80 min and the total injection dose was 4 × 10 16 Pieces / cm 2 ;

[0069] After testing, the Rockwell hardness HRC of the base material polyetheretherketone (PEEK) is 84, and the Rockwell hardness HRC of the surface layer metal copper is 56. The large difference in hardness between the two leads to weak connection at the interface. The relative content of copper in the low-content modified layer of the gradient modified layer prepared in this embodiment is 4.1%, and the hardness is HRC 79; the copper content of the medium-content modified layer is 8.2%, and the hardness is HRC 71; the copper content of the high-content modified layer is 11.3%, and the hardness is HRC 64. On this basis, the adhesion of the copper film deposited by DC magnetron sputtering coating technology is 14.32MPa, which is 61.8% higher than that of the copper film obtained in Comparative Example 1, and the film-base bonding performance has been significantly improved.

[0070] Example 2

[0071] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0072] S1. The substrate was cleaned with an organic cleaning solvent and anhydrous ethanol ultrasonically for 15 minutes each, dried with compressed air for 10 minutes, baked at 100°C for 12 hours, and then placed in a vacuum heating furnace and pre-evacuated to a vacuum chamber with a background vacuum of 2×10 -3 Pa, vacuum heating treatment heated to 100 ° C, keep warm for 2h;

[0073] S2, evacuate the surface of the substrate to a vacuum degree of 2×10 -4 After the temperature is below Pa, the copper cathode source switch is turned on, and inorganic material elements (copper ions) are injected in stages. After the injection is completed, the discharge is stopped, and the vacuum is maintained until the vacuum chamber temperature drops to room temperature. Then, the workpiece is taken out to obtain a polymer material with high energy doping of inorganic material elements.

[0074] The voltage of the low-content doping stage is 30KV, the injection time is 40min, and a low-content doping injection layer is obtained, and the injection layer thickness is 20 to 80nm;

[0075] The voltage of the medium-content doping stage is 20KV, the injection time is 30min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0076] The voltage of the high-content doping stage is 10KV, the injection time is 30min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0077] The total injection time was 100 min and the total injection dose was 5 × 10 16 Pieces / cm 2 ;

[0078] After testing, the Rockwell hardness of the base material polyetheretherketone (PEEK) is HRC 84, and the Rockwell hardness of the surface layer copper is HRC 56. The relative content of copper in the low-content modified layer prepared in this embodiment is 3.8%, and the hardness is HRC 81; the copper content of the medium-content modified layer is 8.0%, and the hardness is HRC 70; the copper content of the high-content modified layer is 15%, and the hardness is HRC 59. On this basis, the adhesion of the copper film deposited by DC magnetron sputtering coating technology is 14.88MPa, which is 67% higher than that of the copper film obtained in Comparative Example 2. The gradient doping layer of soft metal copper element provides a buffer and transition effect for the bearing metal coating (such as Figure 2 -b), effectively improving the membrane-substrate bonding performance.

[0079] Figure 1 The cross-sectional structure diagram of the polymer material of Example 2 is shown in FIG. Figure 1 It can be seen that the changes among low, medium and high content doping layers are gradual.

[0080] The adhesion of the copper film deposited by the polymer material after doping in Example 2 using the DC magnetron sputtering coating technology is 14.32MPa, while the adhesion of the copper film deposited directly on the untreated PEEK substrate using the same technology and process is only 0.58MPa, which is 24 times higher than the surface hardness of the PEEK substrate, significantly improving the performance and service life of the material and workpiece. This is because the surface hardness of the PEEK substrate is 89HS, and the hardness of copper is 71HS. The hardness difference between the substrate and the copper layer is large, which is 18HS, which can easily lead to interface failure (such as Figure 2 -a), after the gradual copper doping was completed by segmented ion implantation, the hardness of the substrate was reduced to 78HS, and the hardness difference between the two was only 7HS, which improved by 39%. The gradual doping layer of the soft metal copper element provided a buffer and transition effect for the bearing metal coating (such as Figure 2 -b), effectively improving the membrane-substrate bonding performance.

[0081] Example 3

[0082] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0083] S1. The substrate was cleaned with an organic cleaning solvent and anhydrous ethanol ultrasonically for 15 minutes each, dried with compressed air for 10 minutes, baked at 120°C for 24 hours, and then placed in a vacuum heating furnace and pre-evacuated to a vacuum chamber with a background vacuum of 3×10 -3 Pa, vacuum heating treatment heated to 120 ° C, keep warm for 3h;

[0084] S2, evacuate the surface of the substrate to a vacuum degree of 4×10 -4 After the temperature is below Pa, the copper cathode source switch is turned on, and inorganic material elements (copper ions) are injected in stages. After the injection is completed, the discharge is stopped, and the vacuum is maintained until the vacuum chamber temperature drops to room temperature. Then, the workpiece is taken out to obtain a polymer material with high energy doping of inorganic material elements.

[0085] The voltage of the low-content doping stage is 15KV, the injection time is 50min, and a low-content doping injection layer is obtained, and the injection layer thickness is 20 to 80nm;

[0086] The voltage of the medium-content doping stage is 15KV, the injection time is 20min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0087] The voltage of the high-content doping stage is 6KV, the injection time is 20min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0088] The total injection time was 90 min, and the total injection dose was 1×1015 Pieces / cm 2 ;

[0089] The relative content of inorganic elements in the low-content doping injection layer is 4%, the relative content of inorganic elements in the medium-content doping injection layer is 9%, and the relative content of inorganic elements in the high-content doping injection layer is 19%.

[0090] Example 4

[0091] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0092] S1. The substrate was cleaned with 1003 organic solvent cleaning agent and anhydrous ethanol ultrasonic cleaning for 15 minutes each, dried with compressed air for 10 minutes, baked at 110°C for 20 hours, and then placed in a vacuum heating furnace and pre-evacuated to a vacuum chamber with a background vacuum of 2×10 -3 Pa, vacuum heating treatment heated to 110 ° C, keep warm for 2h;

[0093] S2, evacuate the surface of the substrate to a vacuum degree of 3×10 -4 After the temperature is below Pa, the copper cathode source switch is turned on, and inorganic material elements (copper ions) are injected in stages. After the injection is completed, the discharge is stopped, and the vacuum is maintained until the vacuum chamber temperature drops to room temperature. Then, the workpiece is taken out to obtain a polymer material with high energy doping of inorganic material elements.

[0094] The voltage of the low-content doping stage is 25KV, the injection time is 45min, and a low-content doping injection layer is obtained, and the injection layer thickness is 20 to 80nm;

[0095] The voltage of the medium-content doping stage is 13KV, the injection time is 25min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0096] The voltage of the high-content doping stage is 7KV, the injection time is 35min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0097] The total injection time was 105 min and the total injection dose was 8 × 10 16 Pieces / cm 2 ;

[0098] The relative content of inorganic elements in the low-content doping injection layer is 4%, the relative content of inorganic elements in the medium-content doping injection layer is 6%, and the relative content of inorganic elements in the high-content doping injection layer is 12%.

[0099] Example 5

[0100] This embodiment is basically the same as Embodiment 2, except that the inorganic material element is chromium.

[0101] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0102] S1. The substrate was cleaned with an organic cleaning solvent and anhydrous ethanol ultrasonically for 15 minutes each, dried with compressed air for 10 minutes, baked at 100°C for 12 hours, and then placed in a vacuum heating furnace and pre-evacuated to a vacuum chamber with a background vacuum of 2×10 -3 Pa, vacuum heating treatment heated to 100 ° C, keep warm for 2h;

[0103] S2, evacuate the surface of the substrate to a vacuum degree of 2×10 -4 After the temperature is below Pa, the chromium cathode source switch is turned on, and inorganic material elements (chromium ions) are injected in stages. After the injection is completed, the discharge is stopped, and the vacuum is maintained until the vacuum chamber temperature drops to room temperature. Then, the workpiece is taken out to obtain a polymer material with high energy doping of inorganic material elements.

[0104] The voltage of the low-content doping stage is 30KV, the injection time is 40min, and a low-content doping injection layer is obtained, and the injection layer thickness is 20 to 80nm;

[0105] The voltage of the medium-content doping stage is 20KV, the injection time is 30min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0106] The voltage of the high-content doping stage is 10KV, the injection time is 30min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0107] The total injection time was 100 min and the total injection dose was 5 × 10 16 Pieces / cm 2 ;

[0108] The relative content of inorganic elements in the low-content doping injection layer is 3%, the relative content of inorganic elements in the medium-content doping injection layer is 8%, and the relative content of inorganic elements in the high-content doping injection layer is 15%.

[0109] Example 6

[0110] This embodiment is basically the same as Embodiment 2, except that the inorganic material element is argon.

[0111] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0112] S1. The substrate was cleaned with an organic cleaning solvent and anhydrous ethanol ultrasonically for 15 minutes each, dried with compressed air for 10 minutes, baked at 100°C for 12 hours, and then placed in a vacuum heating furnace and pre-evacuated to a vacuum chamber with a background vacuum of 2×10 -3 Pa, vacuum heating treatment heated to 100 ° C, keep warm for 2h;

[0113] S2, evacuate the surface of the substrate to a vacuum degree of 2×10 -4 After the temperature is below Pa, inorganic material elements (argon) are injected in stages, and the discharge is stopped after the injection is completed. The vacuum is maintained until the vacuum chamber temperature drops to room temperature, and then the workpiece is taken out to obtain a polymer material with high energy doping of inorganic material elements.

[0114] The voltage of the low-content doping stage is 30KV, the injection time is 40min, and a low-content doping injection layer is obtained, and the injection layer thickness is 20 to 80nm;

[0115] The voltage of the medium-content doping stage is 20KV, the injection time is 30min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0116] The voltage of the high-content doping stage is 10KV, the injection time is 30min, and a low-content doping injection layer is obtained, and the injection layer thickness is 15-70nm;

[0117] The total injection time was 100 min and the total injection dose was 5 × 10 16 Pieces / cm 2 ;

[0118] The relative content of inorganic elements in the low-content doping injection layer is 3%, the relative content of inorganic elements in the medium-content doping injection layer is 8%, and the relative content of inorganic elements in the high-content doping injection layer is 15%.

[0119] Comparative Example 1

[0120] This comparative example is basically the same as Example 1, except that a single modified layer is directly manufactured by ion implantation.

[0121] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0122] S1. The substrate was cleaned with an organic cleaning solvent and anhydrous ethanol ultrasonically for 15 minutes each, dried with compressed air for 10 minutes, baked at 100°C for 12 hours, and then placed in a vacuum heating furnace and pre-evacuated to a vacuum chamber with a background vacuum of 2×10 -3 Pa, vacuum heating treatment heated to 100 ° C, keep warm for 1h;

[0123] S2, evacuate the surface of the substrate to a vacuum degree of 5×10 -4 Pa, the copper cathode source switch was turned on, and inorganic material elements (copper ions) were injected into the separation ion with an injection voltage of 30 KV and a total injection dose of 4 × 10 16 Pieces / cm 2 After the injection is completed, the discharge is stopped, and the vacuum is maintained until the temperature of the vacuum chamber drops to room temperature, then the workpiece is taken out to obtain a polymer material with high energy doping of inorganic material elements.

[0124] After testing, the relative content of copper in the modified layer in this comparative example is 10%, the Rockwell hardness of the modified layer is HRC 69, and the hardness difference with the substrate is 18%. On this basis, the adhesion of the copper film deposited by DC magnetron sputtering coating technology is 8.85 MPa.

[0125] Comparative Example 2

[0126] This comparative example is basically the same as Example 2, except that: no segmented ion implantation is performed, and both the low-content doping stage and the high-content doping stage are replaced by medium-content doping.

[0127] A method for high-energy doping on the surface of a polymer material comprises the following steps:

[0128] S1. The substrate was cleaned with an organic cleaning solvent and anhydrous ethanol ultrasonically for 15 minutes each, dried with compressed air for 10 minutes, baked at 100°C for 12 hours, and then placed in a vacuum heating furnace and pre-evacuated to a vacuum chamber with a background vacuum of 2×10 -3 Pa, vacuum heating treatment heated to 100 ° C, keep warm for 2h;

[0129] S2, evacuate the surface of the substrate to a vacuum degree of 2×10 -4 Pa, turn on the copper cathode source switch, and perform ion implantation with inorganic material elements (copper ions) at an implantation voltage of 30 KV and a total implantation dose of 5 × 10 16 Pieces / cm 2 After the injection is completed, the discharge is stopped, and the vacuum is maintained until the temperature of the vacuum chamber drops to room temperature, then the workpiece is taken out to obtain a polymer material with high energy doping of inorganic material elements.

[0130] After testing, the relative content of copper in the modified layer in this comparative example is 15%, the Rockwell hardness of the modified layer is HRC 59, and the hardness difference with the substrate is 30%. On this basis, the adhesion of the copper film deposited by DC magnetron sputtering coating technology is 8.91 MPa.

[0131] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for high-energy doping on the surface of a polymer material, characterized in that: The steps include: S1, cleaning and baking the substrate, and then performing vacuum heating treatment; S2. Performing segmented ion implantation of inorganic material elements on the surface of the substrate to obtain a polymer material doped with inorganic material elements having a gradually varying relative content.

2. The method for high-energy doping of a polymer material surface according to claim 1, characterized in that: The cleaning in step S1 specifically involves cleaning the substrate with an organic cleaning solvent, and the baking specifically involves baking the cleaned substrate at 80 to 120° C. for 12 to 24 hours.

3. The method for high-energy doping on the surface of a polymer material according to claim 1, characterized in that: The vacuum heating treatment in step S1 is to heat the baked substrate at 2×10 -3 ~4×10 -3 Pa vacuum, heat to 100-120°C and keep warm for 1-4h.

4. The method for high-energy doping on the surface of a polymer material according to claim 1, characterized in that: The segmented ion implantation in step S2 is carried out at a vacuum degree of 5×10 -3 Pa is carried out below.

5. The method for high-energy doping on the surface of a polymer material according to claim 1, characterized in that: The inorganic material elements in step S2 include metal ions and gas ions.

6. The method for high-energy doping on the surface of a polymer material according to claim 5, characterized in that: When the inorganic material element is a metal ion, the cathode metal for injection includes a metal element and an alloy; The metal element includes copper, aluminum, titanium, chromium, nickel or silver; The alloy package is an alloy containing copper, aluminum, titanium, chromium, nickel or silver, and the alloy also includes rare earth elements, rare earth element alloys and rare earth element oxides, and the rare earth element is one or more of scandium, yttrium, praseodymium, lanthanum and cerium.

7. The method for high-energy doping on the surface of a polymer material according to claim 5, characterized in that: When the inorganic material elements are gas ions, the injected gas includes one or more of argon, oxygen, nitrogen and hydrogen.

8. The method for high-energy doping on the surface of a polymer material according to claim 1, characterized in that: The segmented ion implantation is specifically a segmented gradual ion implantation, and the segmented gradual ion implantation includes a low-content doping stage, a medium-content doping stage and a high-content doping stage.

9. The method for high-energy doping on the surface of a polymer material according to claim 8, characterized in that: The voltage of the low-content doping stage is 10-30KV, the injection time is 5-60min, and the injection layer thickness is 20-80nm; the voltage of the medium-content doping stage is 10-20KV, the injection time is 5-40min, and the injection layer thickness is 15-70nm; the voltage of the high-content doping stage is 0-10KV, the injection time is 5-40min, and the injection layer thickness is 15-70nm.

10. The method for high-energy doping on the surface of a polymer material according to claim 8, characterized in that: The total thickness of the low-content doping stage, the medium-content doping stage and the high-content doping stage is 50-220 nm, the total injection time is 15-140 min, and the total injection dose is 1×10 15 ~1×10 17 Pieces / cm 2 .